2014
DOI: 10.1103/physreva.89.052121
|View full text |Cite
|
Sign up to set email alerts
|

Changing quantum reference frames

Abstract: We consider the process of changing reference frames in the case where the reference frames are quantum systems. We find that, as part of this process, decoherence is necessarily induced on any quantum system described relative to these frames. We explore this process with examples involving reference frames for phase and orientation. Quantifying the effect of changing quantum reference frames provides a theoretical description for this process in quantum experiments, and serves as a first step in developing a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 57 publications
1
65
0
1
Order By: Relevance
“…[26] it was shown that quantum mechanics can be consistently formulated without appealing to abstract reference frames of infinite mass. The subsequent literature [27][28][29][30][31][32][33][34] has then focused on different aspects of the introduction of quantum systems as reference frames, and mainly on a) the lack of a shared reference frame, b) bounded-size reference frames, and c) the possibility of overcoming general superselction rules by employing quantum reference frames (e.g., see [27] for a review). These approaches resort to an encoding of quantum information into relational degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%
“…[26] it was shown that quantum mechanics can be consistently formulated without appealing to abstract reference frames of infinite mass. The subsequent literature [27][28][29][30][31][32][33][34] has then focused on different aspects of the introduction of quantum systems as reference frames, and mainly on a) the lack of a shared reference frame, b) bounded-size reference frames, and c) the possibility of overcoming general superselction rules by employing quantum reference frames (e.g., see [27] for a review). These approaches resort to an encoding of quantum information into relational degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%
“…The intended application of the results in this article, as well as one of the primary motivation for this investigation, is to study the act of changing quantum reference frames 6 . Palmer et al [18] have constructed an operational protocol for changing quantum reference frames associated with compact groups. They used the state G[ρ A ⊗ ρ S ] as a relational description of the state ρ S with respect to a quantum reference frame ρ A , and then considered the operation of changing the quantum reference frame from the state ρ A to ρ B .…”
Section: Discussionmentioning
confidence: 99%
“…However, in the framework of non-relativistic quantum information theory the problem of reference frames and of observers is very important [45,46] (see these papers and [47] for the relativistic extension), because for many tasks one needs information on clock synchronization, on the alignment of distinct Cartesian axes and on the determination of global positions. Connected problems are how two unrelated observers Alice and Bob can compare measures of spin when they do not share a common reference frame.…”
Section: Alice and Bob Quantum Observers?mentioning
confidence: 99%
“…In these cases the lack of a reference frame (or its level of imprecision [48]) is treated as a kind of decoherence (or quantum noise) which can wash out all the quantum features of a measurement. See [45,46] for an attempt to define quantum reference frames by quantizing the measuring apparatus associated with a mathematical observer (the previously quoted hybrid description).…”
Section: Alice and Bob Quantum Observers?mentioning
confidence: 99%